2021
DOI: 10.1007/s11010-021-04172-8
|View full text |Cite
|
Sign up to set email alerts
|

BMP4 and PHLDA1 are plausible drug-targetable candidate genes for KRAS G12A-, G12D-, and G12V-driven colorectal cancer

Abstract: Despite the frequent detection of KRAS driver mutations in patients with colorectal cancer (CRC), no effective treatments that target mutant KRAS proteins have been introduced into clinical practice. In this study, we identified potential effector molecules, based on differences in gene expression between CRC patients carrying wild-type KRAS (n = 390) and those carrying KRAS mutations in codon 12 (n = 240). CRC patients with wild-type KRAS harboring mutations in HRAS, NRAS, PIK3CA, PIK3CD, PIK3CG, RALGDS, BRAF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…Previous studies from our group have demonstrated that higher detection of TLR and VDR polymorphisms in CRC patients, especially advanced-stage patients, highlights the role of these polymorphisms in carcinogenesis, disease progression, and ultimately, patient survival [9,10,63]. Regarding DFS, tumors in the sigmoid or right colon and mutations in the ARAF and/or MAPK10 genes were associated with shorter DFS, a fact that has been confirmed in previous studies [64][65][66]. To our knowledge, this is the first study to highlight the role of ARAF and MAPK10 mutations as independent prognostic factors for decreased DFS.…”
Section: Discussionsupporting
confidence: 78%
“…Previous studies from our group have demonstrated that higher detection of TLR and VDR polymorphisms in CRC patients, especially advanced-stage patients, highlights the role of these polymorphisms in carcinogenesis, disease progression, and ultimately, patient survival [9,10,63]. Regarding DFS, tumors in the sigmoid or right colon and mutations in the ARAF and/or MAPK10 genes were associated with shorter DFS, a fact that has been confirmed in previous studies [64][65][66]. To our knowledge, this is the first study to highlight the role of ARAF and MAPK10 mutations as independent prognostic factors for decreased DFS.…”
Section: Discussionsupporting
confidence: 78%
“…These data underscore the importance of the RAS pathway in both UrC and PBAC 16,18,21,27 . The vast majority (11/14) of KRAS mutations were missense mutations in codon 12 (G12V, G12D and G12A) which is a pattern similar to that found in CRC 28 . In recent years, several structural and mechanistic studies have led to the clinical development of selective KRAS inhibitors.…”
Section: Discussionmentioning
confidence: 52%
“… 16 , 18 , 21 , 27 The vast majority (11/14) of KRAS mutations were missense mutations in codon 12 (G12V, G12D and G12A) which is a pattern similar to that found in CRC. 28 In recent years, several structural and mechanistic studies have led to the clinical development of selective KRAS inhibitors. Last year, the FDA granted accelerated approval for sotorasib, the first KRAS ‐blocking drug for patients with non‐small cell lung cancer (NSCLC).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they were reported as potential biomarkers or therapeutic targets for several types of cancers [ 3 , 4 ]. Among TMEMs, TMEM211 is differently expressed between KRAS G12 mutated and wild-type colorectal cancer [ 16 ]. However, its role in colon cancer are still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…TMEM255 was screened for differentially methylated genes and differentially expressed genes, using the TCGA database to obtain gene methylation and gene expression difference in colon cancer samples [ 15 ]. TMEM211 shows different expression levels between KRAS G12 mutated and wild-type colorectal cancer [ 16 ]. However, the particular roles of TMEM211 in colon cancer remain unknown as yet.…”
Section: Introductionmentioning
confidence: 99%